miR-21 may Act as a Potential Mediator Between Inflammation and Abnormal Bone Formation in Ankylosing Spondylitis Based on TNF-α Concentration-Dependent Manner Through the JAK2/STAT3 Pathway - Yu-Cong Zou; Li-Man Yan; Yan-Ping Gao; Zhi- Yun Wang; Gang Liu (SAGE Publishing, 2020)
Objective: To explore the role of microRNA (miR-21) in new bone formation in ankylosing spondylitis (AS) as mediated by different concentration of tumor necrosis factor-α (TNF-α). Methods: Fibroblasts isolated from the hips of patients with AS were induced to osteogenesis. These cells were then stimulated with varying concentrations of TNF-α. MicroRNA-21 expressions were evaluated using reverse transcription-polymerase chain reaction (RT-PCR) and osteogenesis was detected via Alizarin Red S (ARS) staining and measurement of alkaline phosphatase (ALP) activity. Relative expressions of p-STAT3, Nuclear STAT3, cytoplasm STAT3, Runx2, BMP2, osteopontin, osteocalcin, and LC3B in AS fibroblasts were measured after exposure to different concentrations of TNF-α. The STAT3-inhibiting small interfering RNA allowed further exploration on its impact on miR-21 and primary miR-21 expressions. A proteoglycan-induced arthritis (PGIA) Balb/c mouse model was established in order to monitor sacroiliac joint (SIJ) inflammation and subsequent damage through magnetic resonance image. Serum miR-21 and TNF-α expressions were evaluated using RT-PCR and enzyme-linked immunosorbent assay. At week 16, mice models were transfected intravenously with miR-21 overexpressing agomir and miR-21 inhibiting antagomir for 7 successive days. The rate of abnormal bone formation at SIJ was evaluated using microcomputed tomography and hematoxylin and eosin staining at week 24. Western blot analysis enabled quantification of STAT-3, JAK-2, and interleukin (IL)-17A expressions present in the SIJ. Results: The in vitro miR-21 expression and osteogenesis activity were noted to be augmented in the setting of low TNF-α concentrations (0.01-0.1 ng/mL) while they were depressed in settings with higher TNF-α concentrations (1-10 ng/mL). Samples with the most distinct ARS manifestation and ALP activity as well as the highest miR-21 expressions were those who received 0.1 ng/mL of TNF-α. Primary miR-21 was found to be notable raised by Si-STAT3, while the converse effect was seen in mature miR-21 expressions. Intravenous injection of exogenous miR-21 contributed to new bone formation and significantly elevated expressions of STAT3, JAK2, and IL-17 in PGIA mice. Conclusions: The results revealed that miR-21 may act as a potential mediator between new bone formation and inflammation in AS.